2016
DOI: 10.1016/j.scitotenv.2016.06.207
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of restoring longitudinal connectivity for stream fish communities: towards a more holistic approach

Abstract: . (2016) 'Evaluating the eectiveness of restoring longitudinal connectivity for stream sh communities : towards a more holistic approach.', Science of the total environment., 569-570 . pp. 850-860. Further information on publisher's website: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
70
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 81 publications
2
70
1
Order By: Relevance
“…These mixed results align with the few studies that have assessed fish passage restoration success (Pretty et al ; Noonan et al ; Evans et al ; Myers & Nieraeth ; Tummers et al ). Evans et al () found an increase in similarity in fish community composition upstream and downstream of a restored culvert 3 years after restoration, but a decrease in relative fish abundance (though biomass remained constant).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…These mixed results align with the few studies that have assessed fish passage restoration success (Pretty et al ; Noonan et al ; Evans et al ; Myers & Nieraeth ; Tummers et al ). Evans et al () found an increase in similarity in fish community composition upstream and downstream of a restored culvert 3 years after restoration, but a decrease in relative fish abundance (though biomass remained constant).…”
Section: Discussionsupporting
confidence: 72%
“…through insertion of baffles and adjusting culvert slope). In small passage structures such as culverts, resources are rarely put in place to evaluate the biological outcomes of these interventions (Bernhardt et al ; Tummers et al ; Rodeles et al ). This is unfortunate given that these structures are ubiquitous and studies of the impacts of restoration activities are critical to establishing best practices, setting expectations for restoration success and understanding the cost‐benefit analysis of different restoration approaches (see Neeson et al for an example of a return‐on‐investment framework for addressing barrier removal).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Tummers et al. ; Dodd et al. ); therefore, this species may be more adept at navigating the range of flows experienced within fishways with a nature‐like design.…”
Section: Discussionmentioning
confidence: 99%
“…; Calles and Greenberg , ; Tummers et al. ; Dodd et al. ), and 11 studies reported efficiency values for 43 nonsalmonid species at nature‐like fishways (Schmutz et al.…”
mentioning
confidence: 99%